The 2022 monkeypox outbreak: A UK military perspective. Issue 52 (March 2023) - Woolley, S.D.; Dermont, M.; Adam, M.; Pallet, S.J.C.; Reece, N.; Hoysal, N.; Holden, G.; Attridge, K.K.; Fletcher, T.E.; O'Shea, M.K.; Hutley, E.J.; Nicol, E.D.; et al.
Abstract: With the emergence of SARS-CoV-2 and now monkeypox, the UK Defence Medical Services have been required to provide rapid advice in the management of patients with airborne high consequence infectious diseases (A-HCID). The Defence Public Health Network (DPHN) cadre, consisting of closely aligned uniformed and civilian public health specialists have worked at pace to provide evidence-based recommendations on the clinical management, public health response and policy for monkeypox, with military medicine and pathology clinicians (primarily infectious disease physicians and medical microbiologists). Military environments can be complicated and nuanced requiring specialist input and advice to non-specialists as well as unit commanders both in the UK and overseas. DPHN and military infection clinicians have close links with the UK National Health Service (NHS) and the UK Health Security Agency (UKHSA), allowing for a dynamic two-way relationship that encompasses patient management, public health response, research and development of both UK military and national guidelines. This is further demonstrated with the Royal Air Force (RAF) Air Transport Isolator (ATI) capability, provided by Defence to support the UK Government and UKHSA. Military infectious disease clinicians are also embedded within NHS A-HCID units. In this manuscript we provide examples of the close interdisciplinary working of the DPHN and Defence clinicians in managing military monkeypox patients, co-ordinating the public health response, advising the Command and developing monkeypox policy for Defence through cross-government partnership. We also highlight the co-operation between civilian and military medical authorities in managing the current outbreak.